2018
DOI: 10.1177/0883073818787064
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Epileptiform Discharges for Subsequent Epilepsy After Febrile Seizures

Abstract: The predictive value of epileptiform discharges for subsequent epilepsy after febrile seizures was studied in 140 children: 72 children (51%) had simple febrile seizures and 68 children (49%) had complex febrile seizures. Electroencephalography (EEG) was performed in 103 children (74%), it was normal in 66 (47%) and with epileptiform patterns in 37 patients (26%). At follow-up in 2017, 10 children developed epilepsy, 1 had a single epileptic seizure, 9 of them had epileptiform EEGs. Of the patients with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…No study analyzing epileptiform discharge localizations considered the midline-vertex region as a separate region. 8,14,18 Despite the association of midline-vertex discharges with CFS in our study, the presence of midline-vertex discharges do not necessarily predict epilepsy. We noted that similar numbers of patients with midline-vertex discharges on post-CFS EEGs developed and did not develop epilepsy.…”
Section: Discussioncontrasting
confidence: 73%
“…No study analyzing epileptiform discharge localizations considered the midline-vertex region as a separate region. 8,14,18 Despite the association of midline-vertex discharges with CFS in our study, the presence of midline-vertex discharges do not necessarily predict epilepsy. We noted that similar numbers of patients with midline-vertex discharges on post-CFS EEGs developed and did not develop epilepsy.…”
Section: Discussioncontrasting
confidence: 73%
“…Many studies also revealed that EEG might acquire its predictability for subsequent epilepsy in children with abnormal neurologic or developmental status before FS. [28][29][30] In our study, among 10 patients with SES, 5 had epileptiform discharges over the frontopolar regions. Frontal localization has been described as a positive predictor for subsequent epilepsy by other authors 28,[31][32][33] in patients with FS.…”
Section: Discussionmentioning
confidence: 51%
“…In our study, among 10 patients with SES, 5 had epileptiform discharges over the frontopolar regions. Frontal localization has been described as a positive predictor for subsequent epilepsy by other authors 28 31 32 33 in patients with FS.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Further, of those individuals who experienced FSs, the frequency of subsequent development of epilepsy was 2.15-fold greater in females, 4.846-fold greater in patients with recurrent FSs ( Chiang et al, 2018 ). Researchers assessed predictive value of epileptiform discharges for subsequent epilepsy after FSs and found that patients with normal EEGs were unlikely to develop epilepsy ( Kavcic and Rener-Primec, 2018 ). The important impact of FSs on subsequent epileptogenesis has been recognized, but over a large time span, it is clinically difficult to validate directly.…”
Section: The Long-term Adverse Outcomes Associated With Fssmentioning
confidence: 99%